Analisis Risiko dan Mitigasi pada Produk Saqura BMT Bahtera KC Purwokerto - Debby Laura Sendy; Dian Fatimah Azzahra; Desi Dwi Ruswanti; Neli Nurul Azizah; Sulasih, Sulasih; Niken Melani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the risks and mitigation strategies applied to the Saqura product at BMT Bahtera KC Purwokerto. Saqura is a special sharia-based savings product intended for financing aqiqah and qurban worship with a weekly deposit system. This study used a qualitative descriptive method through observation, structured interviews, and documentation. The results showed that the main risks faced include liquidity, operational, reputation, sharia, fund distribution, and external risks. However, the risk level at the Purwokerto branch is still relatively low due to strict management and a routine monitoring system. Mitigation is carried out through the application of the 5C principle (Character, Capacity, Capital, Collateral, Condition), HR training, sharia audits, and cash management and active communication with members. In conclusion, BMT Bahtera KC Purwokerto has good growth potential with effective risk management, supporting the sustainability of the Saqura product and member trust in sharia financial services.